2023
DOI: 10.1101/2023.10.02.560573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOLLO: A genome-scale metabolic reconstruction resource of 247,092 diverse human microbes spanning multiple continents, age groups, and body sites

Almut Heinken,
Timothy Otto Hulshof,
Bram Nap
et al.

Abstract: SummaryComputational modelling of microbiome metabolism has proved instrumental to catalyse our understanding of diet-host-microbiome-disease interactions through the interrogation of mechanistic, strain- and molecule-resolved metabolic models. We present APOLLO, a resource of 247,092 human microbial genome-scale metabolic reconstructions spanning 19 phyla and accounting for microbial genomes from 34 countries, all age groups, and five body sites. We explored the metabolic potential of the reconstructed strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…For example, one could extend the training data substantially by building GEMs for larger collections of genomes, e.g., the full GTDB taxonomy [20], although adding genomes of lower quality could reduce the accuracy of ANN predictions. If one is specifically interested in high-quality predictions for the human gut microbiome, one could apply our approach to very large existing GEM collections of human gut microbes [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one could extend the training data substantially by building GEMs for larger collections of genomes, e.g., the full GTDB taxonomy [20], although adding genomes of lower quality could reduce the accuracy of ANN predictions. If one is specifically interested in high-quality predictions for the human gut microbiome, one could apply our approach to very large existing GEM collections of human gut microbes [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructing eukaryotic metabolism still requires substantial manual curation [2], but automated reconstruction of accurate GEMs from genomes is possible for microbes [3, 4]. Fueled by rapidly growing genomic and biochemical databases [5, 6], automated metabolic reconstruction methods have produced large GEM collections, primarily of human gut microbes [79] but recently of unicellular fungi as well [10]. However, despite progress in metagenomics [11] and cultivation [12], many observed microbes lack genomic data and thus remain inaccessible to GEMs.…”
Section: Introductionmentioning
confidence: 99%
“…49 Finally, differences in gut microbial composition may also contribute to variations in the blood concentration of arginine and its precursors. Accordingly, we found that gut microbiomes from healthy infants were enriched in reactions associated with "Arginine and proline metabolism" compared with healthy adults (average 13.5% ± 2.9% vs 10.7% ± 1.2%) 54 (Table S13). Taken together, this application demonstrates how the infant-WBMs can be personalised based on newborn screening metabolomic data to investigate emerging metabolic properties.…”
Section: Prediction Of Atp Synthase In Different Organsmentioning
confidence: 99%
“…To meet the scale of human gut microbiomes, a resource of genome-scale reconstructions of 773 human gut microbes, called AGORA 18 , was generated and subsequently expanded in size and scope (AGORA2), now accounting for 7,302 human microbes 19 . Additionally, a large-scale reconstruction resource based on metagenomically assembled genomes has been developed accounting for nearly 250,000 genome-scale metabolic reconstructions 20 . Using these microbial reconstruction resources, comprehensive, personalised microbiome models can be constructed using microbial relative abundances derived from metagenomics data through tools, such as the Microbiome modelling toolbox 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%